AN ANALYSIS OF FRAMING STRATEGIES FOR REDEVELOPMENT IN HISTORIC CITIES: AN ASSESSMENT - Kaur, Parminder; Bhandari, Bhandari (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Redeveloping historic cities is an attempt to recognize the social and cultural value of a city and tries to safeguard the authenticity of the city. The cultural heritage of cities can bring people together and create a sense of belonging, while also providing insight into the history and heritage of previous generations. Unfortunately, current development processes are not integrated with the cultural context of cities. The speed and manner of urbanization and modernization disregard the notion of preserving the cultural heritage of cities during redevelopment and instead advocate for a uniform approach to redevelopment that undermines both the existing essence, identity, and atmosphere of the location and the standard of living of the city’s residents. Such an approach ignores the importance of preserving heritage. Therefore, there is a dire need for the government to encourage sensitivity toward heritage preservation while redeveloping historic cities.